Effects of Glycerol and Creatine Hyperhydration on Doping-Relevant Blood Parameters - Polyviou, Thelma P. (MDPI, 2012)
Glycerol is prohibited as an ergogenic aid by the World Anti-Doping Agency (WADA) due to the potential for its plasma expansion properties to have masking effects. However, the scientific basis of the inclusion of Gly as a “masking agent” remains inconclusive. The purpose of this study was to determine the effects of a hyperhydrating supplement containing Gly on doping-relevant blood parameters. Nine trained males ingested a hyperhydrating mixture twice per day for 7 days containing 1.0 g·kg(−1) body mass (BM) of Gly, 10.0 g of creatine and 75.0 g of glucose. Blood samples were collected and total hemoglobin (Hb) mass determined using the optimized carbon monoxide (CO) rebreathing method pre- and post-supplementation. BM and total body water (TBW) increased significantly following supplementation by 1.1 ± 1.2 and 1.0 ± 1.2 L (BM, P < 0.01; TBW, P <0.01), respectively. This hyperhydration did not significantly alter plasma volume or any of the doping-relevant blood parameters (e.g., hematocrit, Hb, reticulocytes and total Hb-mass) even when Gly was clearly detectable in urine samples. In conclusion, this study shows that supplementation with hyperhydrating solution containing Gly for 7 days does not significantly alter doping-relevant blood parameters.